A conceptual model for inter-state corporate waqf financing for higher learning - Shamsudin A.F.; Hashim J.; Wan Yusof W.S.; Yusof A.; Mohamad S.; Yusof A.M.; Zainudin N.H.; Hashim H.; Abidin I.Z. (Kolej University Islam Sultan Azlan Shah, 2023)
Higher education is over dependent on public funds, cash endowments and business contributions which are non-perpetual and may only concern the current and immediate future generations.A resource-based corporate waqf to develop and sustain the higher education sectorwill be explored in this paper.Theresourcebased (from output of harnessing water, energy, land banks and forests) corporate waqf financing are by itself inherently perpetual and sustainable. However, the conventionaltheory of perpetual resource flows across state's borders may constrain the inter-state flow of waqf funds. An Islamic economic theoretical framework of resource-based corporate waqf financing is explored in this study. The optimization of costeffective allocation of burdens of responsibility between many sources (power generators) and receptors (higher education institutions, students) of corporate waqf is modelled. A literature review of Islamic approachesreveal for example, the Islamic principles of Al-Hisbah (administration of public interest) that can minimize the burdens to be shared by the inter-state sourcesand receptors in the interstate model.